2018
DOI: 10.2166/wst.2018.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of toxic metals in water and sediment of Pasur River in Bangladesh

Abstract: This study was conducted to assess the levels of toxic metals like arsenic (As), chromium (Cr), cadmium (Cd), and lead (Pb) in water and sediments of the Pasur River in Bangladesh. The ranges of Cr, As, Cd, Pb in water were 25.76-77.39, 2.76-16.73, 0.42-2.98 and 12.69-42.67 μg/L and in sediments were 20.67-83.70, 3.15-19.97, 0.39-3.17 and 7.34-55.32 mg/kg. The level of studied metals in water samples exceeded the safe limits of drinking water, indicating that water from this river is not safe for drinking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 50 publications
3
38
1
Order By: Relevance
“…High Cd concentrations in the sediments have been shown to be triggered by discharge from electrical plating, metal surface processing, and dying manufacturing industries (Xiao et al 2019). Ali et al (2018) also found that agrochemicals utilized in agriculture were a prominent source of Cd to sediment in this river basin.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…High Cd concentrations in the sediments have been shown to be triggered by discharge from electrical plating, metal surface processing, and dying manufacturing industries (Xiao et al 2019). Ali et al (2018) also found that agrochemicals utilized in agriculture were a prominent source of Cd to sediment in this river basin.…”
Section: Resultsmentioning
confidence: 67%
“…Two Cd hot spots were observed in the northwestern part of the upstream segment at location S5, and in southwestern regions of the downstream segment, with locations S24 and S25 also having high weight for Cd and medium weight for Zn. The elevated Cd might be associated with Cd‐bearing electroplating and welding byproducts that enter the river water, triggering precipitation of contaminants sediment (Ali et al 2018; Niu et al 2020). Thus, it can be inferred that factor 3 is predominantly related to Cd deriving from an industrial point source.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface water bodies are among the most sensitive sources that could be impacted by human activities which may result in degradation of the resource in the future (Afkhami et al, 2013;Roshan et al, 2013). Monitoring of heavy metal contamination in rivers is important because heavy metals pose threat to aquatic life, human health and to the environment due to biomagnification and their toxicity (Ahmed et al, 2015;Ali et al, 2016). The term ''heavy metals" refers to any metallic element that has relatively high density and applies to the group of metals and metalloids with atomic density greater than 5 g/cm 3 (Oves et al, 2012).…”
Section: Introductionmentioning
confidence: 99%